Trade and transport facilitation monitoring mechanism in Nepal baseline study. (Asian Development Bank, 2017)
The establishment of a trade and transport facilitation monitoring mechanism (TTFMM) is important because it allows a country to take stock, identify bottlenecks, and prioritize recommendations for the implementation of trade facilitation measures. A baseline study is the first step to establish TTFMM. This report reviews trade and transport procedures in Nepal, highlights the importance of monitoring trade and transport facilitation, and lays a foundation for future studies and establishment of long term, sustainable TTFMM. In light of the Bangladesh, Bhutan, India, Nepal (BBIN) Motor Vehicles Agreement, the report presents both the challenges and enormous opportunities for enhancing efficiency along the BBIN corridors.